The Quality Analysis of Of Rolled Pancake with Carrot Extract Substitution as Natural Food Colouring - Fatria, Sevly Riri; Holinesti, Rahmi; Gusnita, Wiwik; Andriani, Cici (Jurnal Pendidikan Tata Boga dan Teknologi, 2024)
This research aims to analyze the effect of 0%, 15%, 30% and 45% substitution of carrot extract to the quality of rolled pancakes in terms of shape, color, aroma, texture and taste. This research was conducted in August 2023 at the Culinary Workshop, Department of Family Welfare Sciences, Faculty of Tourism and Hospitality, Padang State University. This type of research is a pure experiment using a completely randomized design method consisting of 4 treatments and 3 repetitions. The data used is primary data obtained from 3 expert panelists using an organoleptic test format on the quality of rolled pancakes with the substitution of carrot extract. The data obtained was then tabulated in table form and analysis of variance (ANOVA) was carried out. If F count > F table then proceed with the Duncan test. The results of this research show that there is a significant effect of substitution of 0%, 15%, 30% and 45% carrot extract on the quality of color and aroma of rolled pancakes. The results of data analysis obtained the highest overall achievement scores, namely: neat shape 3.56 (45%), uniform shape 3.44 (30%), color 3.44 (45%), aroma 3.67 (45%), texture 3.67 (45%) and taste 4.00 (45%). The results of the quality test for rolled pancakes with the best carrot extract substitution were 45% (X3).